Digital Image Processing Application on Shallots Quality Determination - Jane I. Litouw; Feisy D. Kambey; Pinrolinvic D.K. Manembu (Journal of Sustainable Engineering: Proceedings Series, 2019)
Shallot is a horticultural vegetable commodity that has high economic value. North Sulawesi is one of the central production of shallots which has several onion varieties developed and marketed. Technology that can help determine the quality of shallots is needed to simplify the marketing process. This study aims to simulate a system for determining the quality of shallots based on their color and size. The shallot bulb image of several different varieties is input for this system to be able to provide good and bad shallot marks.